Pengaruh Konseling Rasional Emotif Behavior dengan Teknik Role Playing Terhadap Self Succorance - Utari, Putu Devi Ari; Gading, Ketut; Tirka, Wayan (Universitas Pendidikan Ganesha, 2018)
This research is aimed to find out the effect of rational emotif behavior concealing role playing technique toward X grade studentsâ€™ self-succorance at SMA Laboratorium Singaraja. This is quasi experimental research and the design is â€œNonequivalent pretest-postest control groupâ€. Collecting sample in this research is done by purposive sampling. The members of this research sample are 12 students of SMA Laboratorium Undiksha Singaraja which have high self-succorance. Six students were chosen randomly as the experimental group and the other six students as control group. The method that is used in collecting data is questionnaire of self-succorance. The result of this research shows there is an effect of rational concealing emotif behavior role playing technique toward X grade studentsâ€™ self-succorance at SMA Laboratorium Undiksha Singaraja.Â Keywords: Rational Emotif Behavior Concealing, Role Playing Technique, Self Succorance